The impact of livestock ownership on solar home system adoption in the northern and western regions of rural Tanzania - Stephan Klasen; Tukae Mbegalo (Georg-August-Universität Göttingen, Courant Research Centre - Poverty, Equity and Growth (CRC-PEG), 2016)
Livestock has been hypothesized to be one of the major buffer stocks for consumption smoothing in rural areas of developing countries. It is therefore hard for poor farmers in the developing world to finance large investments. We test the latter by estimating a latent variable model of solar home systems. We use off-grid household data from four districts of mainland rural Tanzania. Results indicate that solar adoption is higher for livestock owners than non-livestock owners and that these differences increase as household expenditure increases, but there is no statistical difference at lower- and some middle-expenditure levels. We argue that poor families tend to keep small livestock, which may not generate enough income for investment. They may also decide to accumulate livestock due to a lack of incentives to invest in solar. Furthermore, solar prevalence plays a role in the observed differences of solar adoption. Thus, solar investment financed through livestock will also depend on whether households have enough information on solar technology. In principle, if solar is to spread within a community, households will have to have information on the upfront costs and maintenance costs and the social and economic benefits of solar technology.
Keywords: 330; Livestock; Modern Consumer Goods; Solar Adoption and Solar Home Systems